Flooding hazard in the Tagus estuarine area: The challenge of scale in vulnerability assessments - Tavares, A. (2015)
This paper describes the methodology of the vulnerability assessment to flooding in an estuarine context and presents the final results for the Tagus River estuary, in the metropoli- tan region of Lisbon (Portugal). Performing a local study adapted to a specific type of hazard posed two initial methodological challenges: the selection of the unit of analysis and the identification of the pertinent and available variables. Both challenges were addressed assuming that the area to be assessed should also include the units outside the inundated area, a buffer zone that would include areas indirectly affected. The application of the statistical procedures established in the SoVI1 methodology indicate that certain widely used variables in vulnerability assessments on smaller scales are inadequate at the statistical block scale and that specific variables must be defined and integrated to represent more broadly the dimensions of vulnerability related to social assistance, infrastructures and commutability. The extracted principal components identified the vulnerability drivers in the riverside and surrounding areas. These drivers identify the urban context, the family structure, and the socio-economic condition expressed in terms of housing characteristics, education, mobility and commuting as the dimensions that most differentiate territorial and individuals’ vulnerability. Applications of vulnerability research in risk management are found in the fields of risk communication, stakeholders’ involvement and strategic and operational planning in emergency planning as in other concurring sectors.